APPLICATION OF ALTMAN Z-SCORE METHOD IN PREDICTING FINANCIAL DISTRESS AT PT PINDAD FOR PERIOD 2019–2023 - Sofia Putri Amanda; Anggi Syahadat Harahap; Nur Imam Taufik; Iwan Kurniawan (Journal of Management Small and Medium Enterprises (SMEs), 2026)
PT Pindad, as a strategic state-owned enterprise, plays a crucial role in supporting Indonesia’s national defense industry. This study aims to analyze the company’s financial distress condition using the Altman Z-Score method and to forecast its 2024 financial position through time-series linear regression analysis conducted in Microsoft Excel. The analysis is based on financial statement data covering the period from 2019 to 2023.The findings reveal that PT Pindad consistently remained in the distress zone throughout the observation period, as indicated by its Z-Score results. Forecasting analysis further suggests a continued decline in financial performance in 2024 if no corrective measures are implemented. The Altman Z-Score model demonstrated an estimated predictive accuracy of 80% when compared with actual financial indicators, indicating that the model is relatively reliable in identifying potential financial distress conditions.However, this study is limited to a single company case study, which restricts the generalizability of the findings. Future research is recommended to conduct comparative analyses across multiple firms within the defense industry to provide broader insights. To improve long-term financial sustainability, recommended recovery strategies include debt restructuring, stricter capital expenditure control, operational cost efficiency, and optimization of marketing strategies and asset utilization. Keywords: Financial Distress; Altman Z-Score; Financial Performance